Manajemen Strategi Dewan Kemakmuran Masjid Agung Baitul Makmur Dalam Optimalisasi Fungsi Masjid di Desa Tanjung Keputran Kecamatan Plakat Tinggi Kabupaten Musi Banyuasin - Muhamad Romli; Hidayat HT; Anang Walian (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "Management of the strategy of the Baitul Makmur mosque's prosperity council in optimizing the function of the mosque in Tanjung Keputran village, Plakat Tinggi sub-district, Musi Banyuasin district". The background of this research is the lack of activities and congregations that are present when participating in activities at the mosque held by the prosperity council of the Great Baitul Makmur mosque, Tanjung Keputran village. With the formulation of the problem: How is the strategic management of the Baitul Makmur mosque's prosperity council in optimizing the function of the mosque in Tanjung Keputran village, Plakat Tinggi sub-district, Musi Banyuasin district? This study uses a qualitative descriptive method which includes observation, interviews, and documentation as a means of data collection. Using primary and secondary data. Data analysis techniques used in this study include data reduction, data presentation, and drawing conclusions. In accordance with the results of this study, the strategy management of the prosperity council of the Great Baitul Makmur mosque, Tanjung Keputran village, Plakat Tinggi sub-district, Musi Banyuasin district, carried out by first planning a strategy, implementing the strategy, and evaluating and correcting the strategy. As the strategy carried out by the mosque's prosperity council includes coordinating all members of the mosque's prosperity council, approaching the community, determining activities, determining materials, setting schedules, determining mentors or teachers, and determining learning and study methods. However, the inhibiting factor of this research was the organization of DKM, some members of DKM who could not attend the activity and could not carry out their duties because there were activities that could not be left behind, constrained by distance and location and also the lack of congregations attending the activity. mosque. Keywords: Strategic Management, Optimization, and Mosque Functions.